Heidegger and Language - Powell, Jeffrey, 1954- (Book collections on Project MUSE., 2013)
The essays collected in this volume take a new look at the role of language in the thought of Martin Heidegger to reassess its significance for contemporary philosophy. They consider such topics as Heidegger's engagement with the Greeks, expression in language, poetry, the language of art and politics, and the question of truth. Heidegger left his unique stamp on language, giving it its own force and shape, especially with reference to concepts such as Dasein, understanding, and attunement, which have a distinctive place in his philosophy.